Modular Current Stimulation System for Pre-clinical Studies - Mottaghi, Soheil; Afshari, Niloofar; Buchholz, Oliver; Liebana, Samuel; Hofmann, Ulrich G. (Frontiers in Neuroscience, 2020)
Electric stimulators with precise and reliable outputs are an indispensable part of electrophysiological research. From single cells to deep brain or neu-romuscular tissue, there are diverse targets for electrical stimulation. Even though commercial systems are available, we state the need for a low-cost, high precision, functional, modular (hardware, firmware and software) cur-rent stimulation system with the capacity to generate stable and complex waveforms for pre-clinical research. The system presented in this study is a USB controlled 4-channel modular current stimulator that can be expanded and generate biphasic arbitrary waveforms with 16-bit resolution, high tem-poral precision (µs) and passive charge balancing: the NES STiM (Neuro Elec-tronic Systems Stimulator). We present a detailed description of the system’s structural design, the controlling software, in Saline reliability test and the pre-clinical studies (deep brain stimulation in hemi-PD rat model) in which it was utilized. The NES STiM has been tested with MacOS and Windows op-erating systems. Interfaces to MATLAB source codes are provided. The sys-tem is inexpensive, relatively easy to build and can be assembled quickly. We hope that the NES STiM will be used in a wide variety of neurological applications such as Functional Electrical Stimulation (FES), Deep Brain Stimulation (DBS) and closed loop neurophysiological research.